Dense‐type crypt opening seen on magnifying endoscopy with narrow‐band imaging is a feature of gastric adenoma. Issue 1 (7th April 2013) - Kanesaka, Takashi; Sekikawa, Akira; Tsumura, Takehiko; Maruo, Takanori; Osaki, Yukio; Wakasa, Tomoko; Shintaku, Masayuki; Yao, Kenshi
Abstract : Background: Magnifying endoscopy with narrow‐band imaging (ME‐NBI) can visualize crypt openings (CO) as slit‐like structures in gastric epithelial neoplasia. Visualization of numerous CO is characteristic of low‐grade adenoma (LGA). The aim of the present study was to investigate whether visualization of CO by ME‐NBI is useful for discriminating between LGA and early gastric cancer (EGC). Patients and Methods: Fifty‐one superficial elevated‐type gastric neoplasias (10 LGA and 41 EGC) were retrospectively evaluated. The presence of CO and the number of CO were evaluated in endoscopic photos obtained at high‐power endoscopic magnification by ME‐NBI. The optimal cut‐off value for the number of CO visualized to discriminate between LGA and EGC was determined by receiver operating characteristic curve analysis. Results: The mean number of CO visualized was significantly larger in the LGA group than in the EGC group (31.2, 95% confidence interval [CI] 16.3–46.1 vs 6.3, 95% CI 3.6–9.0; P  < 0.001). When the cut‐off for the number of CO visualized was set at 20, the sensitivity, specificity, and accuracy of dense‐type CO for discriminating between LGA and EGC were 90.0%, 87.8%, and 88.2%, respectively. Conclusion: Determining the number of CO visualized in superficial elevated‐type gastric neoplasias by ME‐NBI appears to be a useful method for discriminating between LGA and EGC.